Interfering with Gal-1–mediated angiogenesis contributes to the pathogenesis of preeclampsia - Freitag, Nancy (2013)
Preeclampsia (PE) is a pregnancy-specific disorder characterized by sudden onset of hypertension and proteinuria in the second half of pregnancy (>20 wk). PE is strongly associated with abnormal placentation and an excessive maternal inflammatory response. Galectin-1 (Gal-1), a member of a family of carbohydrate-binding proteins, has been shown to modulate several processes associated with placentation and to promote maternal tolerance toward fetal antigens. Here, we show that Gal-1 exhibits proangiogenic functions during early stages of pregnancy, promoting decidual vascular expansion through VEGF receptor 2 signaling. Blocking Gal-1– mediated angiogenesis or lectin, galactoside-binding, soluble, 1 de- ficiency results in a spontaneous PE-like syndrome in mice, mainly by deregulating processes associated with good placentation and maternal spiral artery remodeling. Consistent with these findings, we observed a down-regulation of Gal-1 in patients suffering from early onset PE. Collectively, these results strengthen the notion that Gal-1 is required for healthy gestation and highlight Gal-1 as a valuable biomarker for early PE diagnosis.